A study to assess the reading and writing ability of year one students for remedial class at S.K. Dato’ Mohd Musa / Jaliyah Jallil - Jallil, Jaliyah (2008)
This study attempts to assess pupils’ ability in reading and writing in Year One for Remedial Class. It is also an attempt to find out the strengths and problems faced by the pupils in the process of learning and also the educators in the process of teaching. The study involved forty pupils in Year One from S.K. Dato' Mohd Musa, Samarahan. The test papers were set based on the ‘Ujian Saringan’ for ‘Kelas Intervensi Asas Membaca dan Menulis’ which is prepared by the Kementerian Pelajaran Malaysia. In order to ensure the test papers were suitable for the study, the papers were translated into the English Language. The findings and analysis were gathered from the Reading and Writing Filter test. The findings reveal the pupils’ ability in reading and writing in English Language. The data collected is presented using Descriptive Statistics in which they have been quantified using percentage. It is the researcher’s hope that, this study will help pupils and educators in the teaching and learning of the English Language.